Evaluating schema modes and cognitive distortions in borderline personality disorder: A mixed‐method approach. Issue 9 (24th February 2021) - Puri, Priya; Kumar, Devvarta; Muralidharan, Kesavan; Kishore, Madhavaran Thomas
Abstract: Objectives: Cognitive processes, such as schema modes and cognitive distortions, may play a role in the genesis and maintenance of affective, interpersonal, and behavioral difficulties in individuals with Borderline Personality Disorder (BPD). This study aimed at exploring the schema modes and cognitive distortions in individuals with BPD. Methods: Using a mixed‐method approach, 30 individuals with BPD and 30 healthy participants were assessed on the Borderline Personality Questionnaire, the Schema Mode Inventory, the Cognitive Distortions Scale, and a semi‐structured interview schedule. Results: The BPD group had higher scores than the control group on all the maladaptive schema modes and cognitive distortions subscales. The child modes were the commonest and were also the strongest correlate of BPD symptomatology. Qualitative analysis of the content of the semi‐structured interview also corroborated these findings. Conclusions: There could be many schema modes and cognitive distortions operating behind the diverse psychopathology seen in BPD.